1999
DOI: 10.1016/s1074-7613(00)80054-0
|View full text |Cite
|
Sign up to set email alerts
|

Deficient T Cell Fate Specification in Mice with an Induced Inactivation of Notch1

Abstract: Notch proteins are cell surface receptors that mediate developmental cell specification events. To explore the function of murine Notch1, an essential portion of the gene was flanked with loxP sites and inactivation induced via interferon-regulated Cre recombinase. Mice with a neonatally induced loss of Notch1 function were transiently growth retarded and had a severe deficiency in thymocyte development. Competitive repopulation of lethally irradiated wild-type hosts with wild-type- and Notch1-deficient bone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

65
1,089
3
8

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,274 publications
(1,175 citation statements)
references
References 54 publications
65
1,089
3
8
Order By: Relevance
“…To determine the specific cell lineage in which loss of Notch1 contributes to the aortic valve phenotype in Notch1 +/− ;Nos3 −/− mice, we used mice containing a Notch1 ‐floxed allele 26. Because Notch1 is expressed throughout the developing valve mesenchyme in all of the aforementioned lineages, we used Cre‐specific drivers for each cell lineage.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the specific cell lineage in which loss of Notch1 contributes to the aortic valve phenotype in Notch1 +/− ;Nos3 −/− mice, we used mice containing a Notch1 ‐floxed allele 26. Because Notch1 is expressed throughout the developing valve mesenchyme in all of the aforementioned lineages, we used Cre‐specific drivers for each cell lineage.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, none of the loss-of-function studies have demonstrated a role for the Notch/RBP-J signaling pathway in hematopoietic stem cell maintenance. Neither inducible knock-out of RBP-J [68], Notch1 [134] or Jagged1 [135] have led to a reduction of hematopoietic stem cells. In addition, Pear and colleagues showed that HSCs that carry dominantnegative mastermind (dnMAML) can engraft normally in bone-marrow transplantation assays, and that normal frequencies in long-term reconstitution assays are achieved in both the presence or absence of dnMAML [136].…”
Section: Notch In Hematopoiesismentioning
confidence: 99%
“…The importance of Notch signaling for the induction of Tcell fate was first demonstrated in mice in which the Notch1 gene was conditionally deleted using Mx-Cre. These mice exhibited a complete block in T-cell development at an early stage of differentiation and an emergence of ectopic B-cell development in the thymus [134]. Conversely, overexpression of constitutive-active Notch (NICD) in the bone marrow instructed a T-cell fate in bone marrow progenitors and inhibited B-cell development [137].…”
Section: T-cell Developmentmentioning
confidence: 99%
“…For example, this pathway plays an essential role in T cell development; In the absence of either Notch1 or Hes1, T cell development is arrested at the earliest phase before T cell receptor gene rearrangement, indicating that both Notch1 and Hes1 are essential for T cell fate specification [25], [26]. In addition, both Notch1 and Hes1 also regulate later stages of T cell development such as generation of CD8 single-positive cells from CD4CD8 double-positive cells [27], [28].…”
Section: The Notch-hes Pathway In Other Cell Typesmentioning
confidence: 99%